2017
DOI: 10.1016/j.celrep.2017.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Localized Phosphorylation of a Kinesin-1 Adaptor by a Capsid-Associated Kinase Regulates HIV-1 Motility and Uncoating

Abstract: Summary Although microtubule motors mediate intracellular virus transport, the underlying interactions and control mechanisms remain poorly defined. This is particularly true for HIV-1 cores, which undergo complex, interconnected processes of cytosolic transport, reverse transcription and uncoating of the capsid shell. Although kinesins have been implicated in regulating these events, curiously there are no direct kinesin-core interactions. We recently showed that the capsid-associated kinesin-1 adaptor protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 43 publications
7
49
0
Order By: Relevance
“…The second model proposes that capsid undergoes structural changes in the cytoplasm resulting in capsid rupture where a portion of capsid remains intact until disassembly is completed at the nuclear pore, this model agrees with the idea that during trafficking along microtubules, cytoplasmic dynein and kinesin 1, particularly Kif5B, are required for this process as the genetic inhibition of DHC and Kif5B by siRNA, or pharmacological inhibition of dynein function, delayed uncoating, and reduced HIV-1 infection [33]. Furthermore, FEZ1 a kinesin adaptor that bridge HIV-1 cores to Kif5B is important for both traffic and uncoating [31][32][33], were phosphorylation of FEZ1 is required to recruit Kif5B to the HIV-1 cores and to mediate uncoating along movement [32]. If FEZ1 and Kif1B promote uncoating and BicD2 protect from accelerated uncoating and/or rapidly move HIV-1 PIC to the nuclear pore area [28], there must be a highly regulated balance that couples trafficking with uncoating to allow sufficient loss of capsid to permit nuclear entry, but a such a rate that viral DNA is not detected by the antiviral machinery in the cytoplasm.…”
Section: Hiv-1 and Microtubule Associated Proteins At Early Infectionsupporting
confidence: 83%
See 2 more Smart Citations
“…The second model proposes that capsid undergoes structural changes in the cytoplasm resulting in capsid rupture where a portion of capsid remains intact until disassembly is completed at the nuclear pore, this model agrees with the idea that during trafficking along microtubules, cytoplasmic dynein and kinesin 1, particularly Kif5B, are required for this process as the genetic inhibition of DHC and Kif5B by siRNA, or pharmacological inhibition of dynein function, delayed uncoating, and reduced HIV-1 infection [33]. Furthermore, FEZ1 a kinesin adaptor that bridge HIV-1 cores to Kif5B is important for both traffic and uncoating [31][32][33], were phosphorylation of FEZ1 is required to recruit Kif5B to the HIV-1 cores and to mediate uncoating along movement [32]. If FEZ1 and Kif1B promote uncoating and BicD2 protect from accelerated uncoating and/or rapidly move HIV-1 PIC to the nuclear pore area [28], there must be a highly regulated balance that couples trafficking with uncoating to allow sufficient loss of capsid to permit nuclear entry, but a such a rate that viral DNA is not detected by the antiviral machinery in the cytoplasm.…”
Section: Hiv-1 and Microtubule Associated Proteins At Early Infectionsupporting
confidence: 83%
“…-Kinesin-1 adaptor, FEZ1 has been shown to regulate early transport of viral particles by associating to HIV-1 capsid [31]. -Kinesin might also play a role in uncoating of HIV-1 thanks to FEZ1 and Kif5B [32,33].…”
Section: Kinesinmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it was shown that HIV-1 capsid traffics on microtubules on its way to the nucleus (Dharan and Campbell, 2018). HIV-1 capsid uncoating is delayed by destabilization of microtubules or knockdown of microtubule motor proteins kinesin and dynein or NPC protein Nup358 (Dharan et al, 2016;Lukic et al, 2014;Malikov and Naghavi, 2017), suggesting that microtubule trafficking and NPC binding is linked to capsid uncoating. Recent work from several groups suggests that the main uncoating event occurs at or inside the nucleus (Arhel et al, 2007;Burdick et al, 2017;Burdick et al, 2020;Francis and Melikyan, 2018;Zurnic Bonisch et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An important yet understudied aspect of HIV-1 infection, which is referred to as uncoating, describes the process of capsid dissociation that occurs during reverse transcription and before viral DNA integration into host chromatin (Ambrose and Aiken, 2014;Campbell and Hope, 2015). HIV-1 capsid uncoating is dependent on microtubule trafficking (Lukic et al, 2014;Malikov and Naghavi, 2017;Pawlica and Berthoux, 2014) and may occur in a multi-step process (Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%